2021
DOI: 10.3389/fpubh.2021.631749
|View full text |Cite
|
Sign up to set email alerts
|

Assets and Challenges to Recruiting and Engaging Families in a Childhood Obesity Treatment Research Trial: Insights From Academic Partners, Community Partners, and Study Participants

Abstract: Background: There is need for the childhood obesity treatment literature to identify effective recruitment and engagement strategies for rural communities that are more likely to lack supportive infrastructure for healthy lifestyles and clinical research relative to their urban counterparts. This community case study examines recruitment and engagement strategies from a comparative effectiveness research (CER) trial of two family-based childhood obesity (FBCO) treatment interventions conducted in a medically u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…Second, we found that interviewees also valued support for interorganizational collaboration. These findings may be due to the unique focus on micropolitan and rural communities, and align with previous research examining FHWPs in micropolitan and rural areas, where members of a community advisory board highlighted the development of sustainable referral protocols that relied on engagement across community organizations [ 1 ].…”
Section: Discussionsupporting
confidence: 82%
“…Second, we found that interviewees also valued support for interorganizational collaboration. These findings may be due to the unique focus on micropolitan and rural communities, and align with previous research examining FHWPs in micropolitan and rural areas, where members of a community advisory board highlighted the development of sustainable referral protocols that relied on engagement across community organizations [ 1 ].…”
Section: Discussionsupporting
confidence: 82%
“…Detailed description of our engagement findings are published elsewhere. 48 In brief, key participant-level factors influencing engagement included scheduling conflicts to attend synchronous sessions in a set location, geographical distances and lack of transportation, unexpected life events, dissatisfaction with the randomized programme assignment or exclusionary eligibility criteria, and conflicting family prioritization of lifestyle changes. Also, our findings indicate future opportunities to assess attendance barriers and readiness to make changes prior to enrollment and to help families set and monitor attendance goals.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to our previous single‐group 3‐month pilot trial of i Choose ( n = 101 families, retention = 72%, 43% family class attendance, 62% call completion, 33% physical activity class attendance) in this region, 14 we were not any more successful with the addition of a PAT and other deliberate engagement and retention strategies for this trial (see Figure 1)—suggesting that programme features may be stronger predictors of engagement than the social support strategies targeting engagement. Detailed description of our engagement findings are published elsewhere 48 . In brief, key participant‐level factors influencing engagement included scheduling conflicts to attend synchronous sessions in a set location, geographical distances and lack of transportation, unexpected life events, dissatisfaction with the randomized programme assignment or exclusionary eligibility criteria, and conflicting family prioritization of lifestyle changes.…”
Section: Discussionmentioning
confidence: 99%
“…17 To the authors' knowledge, only 2 studies investigating recruitment to weight-management intervention research among systematically marginalized youth include the voices/perspectives of the youth, 7,10 and none combine youth perspectives with those of other community stakeholders. By building upon existing community-engaged research frameworks, 8,22 this study seeks to help fill that gap by weaving together the perspectives of multiple stakeholder groups and, notably, highlighting the perspectives of youth to explore facilitators and barriers in recruiting systematically marginalized families in weight management studies. Specifically, this study explored perspectives of stakeholders on both recruitment materials and processes for 1 weight-management intervention study.…”
Section: Current Studymentioning
confidence: 99%
“…Although research has been done exploring facilitators and barriers to health-related research participation among systematically marginalized adults, [18][19][20][21] and there are studies of perspectives of parents concerning recruitment of youth into a weight management trial, 8,11,15 few studies have simultaneously explored various stakeholder perspectives in the recruitment of systematically marginalized youth into weight management trials. The 2 studies that examined various stakeholder perspectives on youth involvement in weightmanagement research were conducted with rural 22 and white Australian populations. 17 To the authors' knowledge, only 2 studies investigating recruitment to weight-management intervention research among systematically marginalized youth include the voices/perspectives of the youth, 7,10 and none combine youth perspectives with those of other community stakeholders.…”
Section: Current Studymentioning
confidence: 99%